Anti-poverty transfers without riots in Tunisia - Christophe Muller (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
We draw some lessons from the Tunisian experience of social reforms and associated civil conflict. Our main interest is the riots that occurred after subsidy cuts and their possible substitution of price subsidies by direct cash transfers. We propose new welfare indicators apt to assess policy reforms in situations of fragile states. Finally, using micro level data we show that the plausible policy decision depend on parameters describing the balance between poverty and program exclusion risk. In the Tunisian case, only a much larger weight put on poverty relatively to exclusion could bring the decision maker to substitute the in force price subsidies with direct cash transfers, for fear of social unrest.
Keywords: D63; H53; I38; 330; Poverty; Social conflicts; Tunisia; Targeting; Social transfers; Sozialhilfe; Sozialer Konflikt; Armut; Schätzung; Tunesien